GROWTH AND YIELD OF SOYBEAN (Glycine Max. L. Merril) AS INFLUENCED BY COMBINED APPLICATION OF BIOCHAR AND MICRONUTRIENT (FUDMA JOURNAL OF SCIENCES, 2022)
The experiments were conducted at the Teaching and Research Farm, Faculty of Agriculture, Shabu–Lafia Campus of Nasarawa State University, Keffi, during the 2018 and 2019 cropping seasons to examine the integrated effects of biochar and micronutrient on the growth and yields of soybean. The experiments were laid in Randomized Complete Block Design (RCBD with three replications. Biochar at the rates of 0, 4, 8 and 12 tons/ha was incorporated into the ridges before planting the soybean seeds. Micronutrient at the rate of 0.0, 0.5 and 1 litre/ha was foliar applied two weeks after planting. All data collected were subjected to analysis of variance (ANOVA) using GENSTAT Statistical Package while least significant different (LSD) was used to separate treatment means at 5 % level of probability. The results revealed that biochar at the rate of 8 tons/ha, when combined with micronutrient at the rate of 0.5 litre/ha, recorded significantly (P
Keywords: Biochar, integrated, growth, soybean, yield